Panchromatic and Multispectral Image Fusion by Combining IHS Transform and Haar Wavelet - Hamed, Alaa A.; Al-Safar, Amna; Taha, Namar A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The technique of integrate complimentary details from two or more input images is known as image fusion. The fusion image is more informational and will be complete more than any of the original input images. This paper Illustrates implementation and evaluation of fusion techniques used on the Satellite images a high-resolution Panchromatic (Pan) and Multispectral (MS). A new algorithm is proposed to fuse a Pan and MS of the lowresolution images based on combining IHS and Haar wavelet transform.Firstly, this paper clarifies the classical fusion by using IHS transform and Haar wavelet transform individually. Secondly proposition new strategy of combining the two methods. Performance of the proposed method is evaluated with the help of assessment parameter such as Mean Square Error and Peak Signal to Noise Ratio. Experiment results shows that the proposed algorithm has higher performance than the classical fusion by IHS transform.